Identification of DNA adducts of methylglyoxal - Frischmann, Matthias; Bidmon, Clemens; Angerer, Jürgen; Pischetsrieder, Monika (Chemical Research in Toxicology, 2005)
Methylglyoxal (MG) is a sugar degradation product, which is endogenously formed by fragmentation of triose phosphates during glycolysis, ketone body metabolism of acetone, and catabolism of threonine. Food, beverages, and medical products are important exogenous sources with concentrations of up to 100 μM MG. MG is a reactive dicarbonyl compound, which easily modifies amino groups of proteins (glycation reaction) and thereby induces proinflammatory responses. Moreover, increased mutation frequencies in mammalian cells after treatment with MG have been reported, which are caused by stable modifications of DNA bases. Thus far, two types of adducts have been identified, which are formed during the reaction of free guanine or 2′-deoxyguanosine with high MG concentrations. In this study, we investigated the prolonged exposure of DNA to physiological MG concentrations. DNA was incubated with MG, enzymatically hydrolyzed to release the free nucleosides, and then analyzed by LC-MS/MS. We detected four products, which were derived from the reaction of 2′-deoxyguanosine and 2′-deoxyadenosine with 1 and 2 equiv of MG each. The adducts with 1 equiv of MG were identified as N2-(1- carboxyethyl)-2′-deoxyguanosine (CEdG) and N6-(1-carboxyethyl)- 2′-deoxyadenosine. LC-MS/MS was optimized for these compounds, and incubation of DNA was repeated using physiological concentrations of 10 μM MG. Thereby, CEdG proved to be the most sensitive and suitable marker for the reaction of DNA with MG (negative MRM mode, three mass transitions [M - 1] - 338→178, 338→106, and 338→149). © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.identi

Mercapturic acids of acrylamide and glycidamide as biomarkers of the internal exposure to acrylamide in the general population - Böttcher, Melanie; Schettgen, Thomas; Kütting, Birgitta; Pischetsrieder, Monika; Angerer, Jürgen (Mutation Research-Genetic Toxicology and Environmental Mutagenesis, 2005)
Acrylamide (AA), a widely used industrial monomer which is categorised to be carcinogenic, was found to be generated in starch-containing foods during the heating process. This discovery has caused reasonable concern about possible health risks to humans due to dietary acrylamide uptake. In order to gain more information on human metabolism of acrylamide and to contribute to the assessment of the human carcinogenic risk due to AA uptake we measured the mercapturic acid of AA and its epoxide glycidamide (GA) i.e. N-acetyl-S-(2-carbamoylethyl)-l-cysteine (AAMA) and N-(R,S)-acetyl-S-(2- carbamoyl-2-hydroxyethyl)-l-cysteine (GAMA) in human urine. The relation between AAMA and GAMA is important in this context because GA is thought to be the ultimate carcinogenic metabolite of AA. The median levels in smokers (n = 13) were found to be about four times higher than in non-smokers (n = 16) with median levels of 127 μg/l versus 29 μg/l for AAMA and 19 μg/l versus 5 μg/l for GAMA. Therefore cigarette smoke proved to be an important source of acrylamide exposure. The level of AAMA in the occupationally non-exposed collective (n = 29) ranged from 3 to 338 μg/l, the level of GAMA from
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.mercap
Keywords: Acrylamide; Biological monitoring; General population; Mercapturic acids; Metabolism; Risk estimation

Pilot study on the naphthalene exposure of German adults and children by means of urinary 1- and 2-naphthol levels - Preuß, Ralf; Koch, Holger; Wilhelm, Michael; Pischetsrieder, Monika; Angerer, Jürgen (International Journal of Hygiene and Environmental Health, 2004)
Concentrations of 1- and 2-naphthol were measured in urine of 72 adults and 35 young children from Germany to assess the internal exposure to naphthalene of the general population. Naphthols could be detected in more than 90% of the urine samples. Levels of naphthols (sum of 1- and 2-naphthol) were 4-fold higher in smokers (median: 37.6 μg/g creatinine) compared to non-smoking adults (8.2 μg/g creatinine). On a creatinine basis young children had slightly lower naphthol levels in urine compared with adults (7.5 μg/g creatinine). Preliminary reference values for the sum of 1- and 2-naphthol in urine as means of the 95th percentile are proposed: 41.2 μg/g creatinine (non-smoking adults) and 23.5 μg/g creatinine (young children). It is concluded that 1- and 2-naphthol levels in urine are suitable for human biomonitoring of the naphthalene exposure in environmental medicine.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.pilots
Keywords: Adults; Biological monitoring; Children; Environmental medicine; Metabolites; Naphthalene; Naphthol; Urine